Optical properties of Pb0.52Zr0.48TiO3 nanorod arrays: second harmonic generation and multiphoton carrier dynamics. (10th June 2021) - Mudiyanselage, Rathsara R H H; Burton, John; Magill, Brenden A; McMillan, Kiara; Gagliano, Gabriella; Morral, Ada J; Gyu Kang, Min; Kang, Han Byul; Priya, Shashank; Stanton, Christopher J; Khodaparast, Giti A
Abstract: Nonlinear optical properties of poled and unpoled, lead zirconate-titanate (Pb0.52 Zr0.48 TiO3 ) nanorod arrays, grown on Pt-coated Si with ∼200 nm diameter and ∼600 nm height, were investigated. Clear signatures of second harmonic generations (SHG), from 490–525 nm (2.38–2.53 eV) at room temperature, were observed. Furthermore, time resolved differential reflectivity measurements were performed to study dynamical properties of photoexcited carriers in the range of 690–1000 nm where multiphoton processes were responsible for the photo-excitations. We compared this excitation scheme, which is sensitive mainly to the surface states, to when the photoexcited energy (∼3.1 eV) was close to the band gap of the nanorods. Our results offer promises for employing these nanostructures in nonlinear photonic applications.